2022
DOI: 10.7461/jcen.2022.e2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transarterial n-BCA and Onyx embolization of brain arteriovenous malformations: A single-center 18-year retrospective analysis

Abstract: Objective: Brain arteriovenous malformations (AVM) are commonly treated with endovascular embolization. Due to the rapid evolution of endovascular technology and lack of consistent practice guidelines regarding AVM embolization, further study of AVM embolization outcomes is warranted.Methods: We conducted a retrospective review of AVMs embolized at a single center from 2002-2019. Patient demographics, AVM characteristics, intention of embolization, and angiographic and clinical outcome after embolization were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other authors have shown similar results. [2,9] e present case is unique in its extradural and cervical location, the associated presenting symptoms being radicular versus myelopathic, and highlights another viable endovascular approach to these rare lesions. It is of clinical interest for vascular neurosurgeons and interventional radiologists to define these lesions and continue to add to the literature of successful treatment using endovascular approaches.…”
Section: Discussionmentioning
confidence: 82%
“…Other authors have shown similar results. [2,9] e present case is unique in its extradural and cervical location, the associated presenting symptoms being radicular versus myelopathic, and highlights another viable endovascular approach to these rare lesions. It is of clinical interest for vascular neurosurgeons and interventional radiologists to define these lesions and continue to add to the literature of successful treatment using endovascular approaches.…”
Section: Discussionmentioning
confidence: 82%
“…Liquid embolization is most commonly utilized to treat arteriovenous malformations and fistulae, but has also been employed for intracranial aneurysms ( 69 ). Around the time of the first stand-alone coiling procedures, some clinicians began utilizing liquid embolization materials in tandem with other space-occupying embolic materials.…”
Section: Liquid Embolicsmentioning
confidence: 99%
“…We read with great interest the recent article by Behzadi and colleagues entitled “Comparison of transarterial n-Butyl cyanoacrylate (n-BCA) and Onyx embolization of brain arteriovenous malformations: A single-center 18-year retrospective analysis” [ 2 ]. We believe their principal finding of high safety when pursuing embolization using Onyx and n-BCA to be both encouraging and reflective of appropriate patient selection for standalone embolization treatment of brain arteriovenous malformations (AVMs).…”
Section: To the Editormentioning
confidence: 99%